Dopamine-derived nanoparticles for the protection of irradiation-induced intestinal injury by maintaining intestinal homeostasis. (19th May 2022) - Jia, Shuhan; Dong, Suhe; Liu, Heng; Yu, Huijie; Chen, Zhongmin; Wang, Sinian; Li, Wei; Peng, Renjun; Li, Fengsheng; Jiang, Qisheng; Liu, Jianjun
Abstract : PDA-NPs improved the intestinal epithelium and maintained the intestinal barrier function after irradiation, in which PDA-NPs prevented the depletion of Lgr5 + ISCs and suppressed apoptosis, pyroptosis and DNA damage. Abstract : Radiotherapy of abdominal and pelvic tumors almost inevitably injures the intestine by oxidative stress and causes inflammation. Regrettably, traditional radioprotective agents for irradiation (IR) induced intestinal injury suffer from challenges such as poor solubility, unsatisfactory bioactivity and undesired adverse reactions, which significantly limit their usefulness. Polydopamine nanoparticles (PDA-NPs) have shown promising potential in scavenging reactive oxygen species (ROS) and suppressing inflammation. In this study, PDA-NPs were prepared by a simple method and their physical properties were characterized. Mice received two doses of PDA-NPs by oral gavage 22 h apart, and were irradiated with X-rays 2 h after the last gavage. The protective effect of PDA-NPs and possible mechanisms of protection against IR-induced intestinal injury were explored. The results showed that PDA-NPs were spherical and well dispersed, with good shape uniformity, compact structure, good colloid dispersion stability, concentration-dependent light absorption, and accurate quantification. Importantly, PDA-NPs reduced mortality and prolonged the average survival time of mice after IR. Furthermore, PDA-NPs protected mice from IR-induced injury to crypt–villus units and maintained intestinal barrier function in the intestine. In particular, PDA-NPs significantly inhibited the depletion of Lgr5 + intestinal stem cells (ISCs) and promoted cell regeneration after IR, which indicated that the regeneration ability of ISCs was maintained and the repair of intestinal structure and function was promoted. Finally, PDA-NPs significantly suppressed the apoptosis, inflammatory pyroptosis and DNA damage of intestinal cells induced by ionizing radiation. Altogether, our study suggested that PDA-NPs may have great potential in protecting the intestines from ionizing radiation damage.